In vitro study of a biological prosthetic valve for seamless fixation - K. U. Klyshnikov (Vestnik Transplantologii i Iskusstvennyh Organov, 2018)
Aim: to evaluate the manipulative properties of the system being developed for cardiac valve re-operation on an in vitro bovine heart model.Material and methods. The prototype of the prosthesis being developed, mounted on the implant holder, as well as the dilatation balloon of its own design, were used as the objects of the study. The bioprosthesis «UniLine» of 21 mm size for the aortic position was chosen as the target site of implantation, which was established by the «classical» suture method. After that, the implantation of the tested device was carried out as a «valve in valve» and the quality of the installation and the combined operation of all the components of the re-prosthesis system were evaluated.Results. The test implantation demonstrated the consistency of the proposed method on the basis of balloon seamless ﬁ xation, as well as high ergonomic characteristics: the average time of seamless implantation of the developed prototype on an in vitro animal heart model was 3 minutes versus the implantation of the «UniLine» bioprosthesis – 11 min, Implantation provided a reliable prosthesis The breaking force was 12.9 N, which is equivalent to a pressure of 279 mm Hg.